THE VALUE CHAIN ANALYSIS OF COFFEE PRODUCTION AT PT. FORTUNA INTI ALAM - Bachmid, Feety F.; Saerang, David P.E; Pandowo, Merinda Ch. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Value-chain business activities are divided into primary activities and secondary activities. And from those activities, companies build a competitive strategy for improving product or services. This research aims to analyze the value chain in a coffee factory. The purpose of this study is to analyze the implementation of the value chain in the coffee factory at PT. Fortuna Inti Alam. This research uses qualitative research that explores theories from several journals, articles, books and previous research. So, the type of this research is descriptive research and it describes or explains the two categories of the value chain inside. The result of this thesis regarding of PT. Fortuna Inti Alam is found the lack in several activities inside the company. From primary activities are the marketing & sales, inbound logistics and service. While in Support activities are the technology development and HRM. But in the other way technology development is also have an advantage and following with the rest of several activities inside. The recommendation for the company is about improving several activities that still lack and need an improvement to maximize companyâ€™s performanceÂ Keyword: value chain analysis, factory, support activity, primary activityÂ